Integrating behavioral science into urban planning: a framework for human-centered spatial design - Mohamed M. E. Khogali; Eman Ahmed Mohamed Ali; Abbas Ramdani (Frontiers in Psychology)
This paper examines the intrinsic relationship between urban planning and behavioral concepts, addressing a significant knowledge gap in how spatial arrangements influence human behavior and well-being. Through a systematic literature review and analytical framework, we investigate the interdependence between urban spatial design and human behavioral patterns across seven key planning domains: urban form, built environment, infrastructure services, urban landscapes, public spaces, urban housing fabric, and urban design. Our findings reveal that physical environments significantly shape human psychological, cognitive, and behavioral responses, while human activities simultaneously influence urban structures. The research identifies critical behavioral determinants that impact urban environments and demonstrates how behavioral science can reduce uncertainty in design processes. By integrating insights from environmental psychology and behavioral theory, this study offers a conceptual model to guide urban planners toward more behaviorally responsive design approaches. We conclude that well-planned cities support economically prosperous, socially cohesive, and environmentally sustainable communities, while poorly planned environments can exacerbate social unrest and hinder development. The study recommends institutionalizing participatory design methodologies, prioritizing pedestrian-oriented layouts, equitably distributing green spaces, adopting context-sensitive planning approaches, and implementing rigorous post-implementation behavioral assessments to develop truly human-centered urban environments.